Investigation of a NACA0012 Finite Wing Aerodynamics at Low Reynold’s Numbers and 0º to 90º Angle of Attack - Shahrooz Eftekhari (Journal of Aerospace Technology and Management, 2019)
The aerodynamic characteristics of a NACA0012 wing geometry at low Reynold’s numbers and angle of attack ranging from 0º to 90º are investigated using numerical simulations and the results are validated by wind tunnel experiments. Further experiments are conducted at low Reynold’s numbers of 1 × 105, 2 × 105 and 3 × 105. Findings of the study show a similar trend for the lift and drag coefficients at all the investigated Reynold’s numbers. The lift coefficient is linearly increased with angle of attack until it reaches its maximum value at 32º which is the stall angle. It is observed that further increment in angle of attack results in decrement of lift coefficient until it reaches its minimum value at 90º angle of attack. The drag force acting on the airfoil increases as the angle of attack is increased and increment in the drag force results in change of laminar flow to turbulent flow. As the turbulence gets higher the flow starts to separate from the airfoil surface due to eddies generated by turbulence. Hence, the lift force generated by the wing is reduced and drag force is increased simultaneously, which results in poor performance of the wing.